Changes in the estimated glucose disposal rate and incident cardiovascular disease: two large prospective cohorts in Europe and Asia - Zheng, Xiaowei; Han, Wenyang; Li, Yiqun; Jiang, Minglan; Ren, Xiao; Yang, Pinni; Jia, Yiming; Sun, Lulu; Wang, Ruirui; Shi, Mengyao; Zhu, Zhengbao; Zhang, Yonghong (Cardiovascular diabetology, 2024)
Previous study found that estimated glucose disposal rate (eGDR) was significantly associated with cardiovascular disease (CVD). However, little is known about the change in eGDR over time and its association with the development of CVD. The aim of this study was to investigate the association of change in eGDR with CVD risk. This study used data of two prospective cohorts: UK Biobank and China Health and Retirement Longitudinal Study (CHARLS) with two measurements of eGDR. Changes in the eGDR were classified using K‑means clustering analysis, and the cumulative eGDR was also calculated. Cox proportional hazard models were used to calculate the hazard ratio (HR) and 95% confidence interval (95% CI) after adjusting for potential confounders. A total of 11,682 individuals from the UK Biobank, and 4,974 individuals from the CHARLS were included. The median follow-up periods were 9.7 years in the UK Biobank and 3.0 years in the CHARLS. Compared with persistently high level of eGDR (class 1), individuals with low level increasing (class 3) and persistently low level of eGDR (class 4) showed elevated risks of incident CVD in both UK Biobank (HR = 2.79, 95% 2.15-3.62 for class 3; HR = 3.19, 95% 2.50-4.08 for class 4) and CHARLS (HR = 1.66, 95% 1.29-2.13 for class 3; HR = 1.69, 95% 1.34-2.14 for class 4). In addition, lower level of cumulative eGDR were associated with elevated risks of incident CVD. The dose-response curve between cumulative eGDR and CVD risk showed a negative linear relationship. Different changes in eGDR level are associated with different risks of incident CVD. Dynamic monitoring of eGDR level is of significant importance for the CVD prevention and treatment.